Anti-radiation solar cell front panel and preparation method thereof
By using PET film on the front panel of the polymer composite solar cell with a fluorocarbon resin protective film and applying a specific radiation-proof coating on the outside, the ultraviolet light and thermal curing process are used to solve the ultraviolet light on the polymer composite front panel. The sensitivity problem has achieved excellent radiation resistance and visible light transmittance.
Patent Information
- Application Number
- CN202311779124.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-21
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2043-12-21
AI Technical Summary
The front panels of existing polymer composite solar cells lack effective protection when facing ultraviolet radiation, resulting in a decrease in power generation efficiency. The limitations of traditional radiation-proof films in light transmission function are not suitable for use in front panels.
The PET film and the fluorocarbon resin protective film are bonded together through an adhesive layer, and a radiation-proof coating is applied to the outside of the fluorocarbon resin protective film. The coating is made of ethylene-vinyl acetate copolymer resin and polydine. Diene polyurethane, polyacrylate resin, composite ultraviolet absorber and initiator are composed of to improve radiation resistance through ultraviolet light and thermal curing processes.
Excellent radiation resistance and good visible light transmittance are achieved, avoiding the power generation efficiency of the front panel due to the influence of ultraviolet light, and ensuring the uniformity and transparency of the film layer.
Smart Images

Figure CN119283469A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of solar cells, and in particular to a solar cell front plate made of a composite polymer material, and more particularly to a radiation-proof solar cell front plate and a preparation method thereof. Background Art
[0002] Photovoltaic modules are usually composed of front panels, packaging materials, solar cells, back panels and other structures; the back panel is used to protect the solar cell modules from water vapor erosion and prevent internal oxidation of the modules. It must have reliable insulation, water resistance, aging resistance, high and low temperature resistance, corrosion resistance, etc. The front panels are mostly made of glass, which has high strength and good light transmittance. The glass front panel has the disadvantages of being heavy and unable to bend greatly. Polymer materials are increasingly attracting attention as front panel materials instead of glass. Existing polymer composite front panels are generally made of fluorocarbon resin and PET base film to form a transparent front panel.
[0003] The polymer composite front panel is similar to the multi-layer back panel structure, so most technicians assume that the front panel is made of glass, or that the front panel and the back panel are the same, so few people pay attention to the problems that the front panel needs to face. Generally speaking, the back panel is set on the back of the solar panel and plays a more supporting role. It does not require high light transmittance, and because it is not directly exposed to the sun, it is much less affected by solar radiation than the front panel.
[0004] CN 203134840 U discloses a radiation-proof double-glass solar cell module, including a back plate glass located at the lower layer of a solar cell sheet, and a radiation-proof film is provided on the back plate glass. This prior art considers the problem that the glass back plate in the double-glass solar cell module has a low ultraviolet light blocking rate. The radiation-proof film provided is a 10-layer coated nano-metal film, and its ultraviolet light blocking rate is greater than 65%, and the visible light transmittance is not less than 75%. Obviously, if this radiation-proof film is applied to the front plate, the power generation efficiency of the solar cell will directly drop by about 25%. It can be seen that the radiation-proof metal film is not suitable for use on the front plate of a solar cell whose basic function is light transmission.
[0005] CN 106952978 A discloses a photovoltaic module, including a silicon wafer cell, a PET composite film with a three-layer structure is encapsulated on the upper and lower surfaces of the silicon wafer cell, a back plate is provided above the upper surface PET composite film and below the lower surface PET composite film, a reflective layer is provided above the back plate above the upper surface PET composite film and below the back plate below the lower surface PET composite film, a photovoltaic glass is provided above the reflective layer above the back plate and below the reflective layer below the back plate, and a radiation-proof metal film is provided on the outer surface of the photovoltaic glass. The prior art sets a reflective layer on both sides of the cell, and sunlight cannot reach the cell at all. Although a radiation-proof metal film is set on the outer surface, the metal film has little difference in weakening effect on light of different wavelengths, and while preventing radiation, it will also reduce the power generation efficiency of the solar cell.
[0006] CN 112812695 B A packaging film for photovoltaic modules, comprising the following raw material components: base resin, crosslinking agent, auxiliary crosslinking agent, silane coupling agent and light stabilizer; the auxiliary crosslinking agent comprises a combination of isocyanate auxiliary crosslinking agent and acrylate auxiliary crosslinking agent. The preparation method of the packaging film comprises the following steps: mixing the base resin, crosslinking agent, auxiliary crosslinking agent, silane coupling agent and light stabilizer and optional filler, photoinitiator, silane coupling agent, ultraviolet light absorber and anti-PID auxiliary agent, and extruding to obtain the packaging film. The ultraviolet light absorber is selected from any one of UV-326, UV-327, UV-328, UV-329, UV-360, UV-P, UV-234, UV-1130, UV-384-2, UV-928, UV-400, UV-1577, UV-1164 or UV-531 or a combination of at least two thereof. The prior art encapsulation film is a layer of ultraviolet light absorber between the glass front plate and the back plate, and its purpose is to wrap the battery cell. However, the ultraviolet light absorbed by this encapsulation structure obviously penetrates the front plate. If the front plate adopts a polymer composite film, the polymer film in the front plate will be affected by the ultraviolet light and cannot provide radiation protection for the front plate.
[0007] CN 102867872 B discloses a POE-containing solar cell backplane and a preparation method thereof, wherein the backplane comprises a weather-resistant layer, an adhesive layer, a structural reinforcement layer, and a POE adhesive film layer; the components of the POE adhesive film layer are: POE, POE grafted maleic anhydride copolymer, an initiator, an ultraviolet light absorber, an ultraviolet light stabilizer, and an antioxidant. The ultraviolet light absorber is 2-hydroxy-4-methoxybenzophenone, 2,4-dihydroxybenzophenone, 2-hydroxy-4-n-octyloxybenzophenone or 2-(2′-hydroxy-5′-tert-octylphenyl)-benzotriazole. This prior art is aimed at the problem of backplane UV protection, and does not need to consider the problem of high-dose ultraviolet radiation, nor does it need to consider the problem of light transmittance. In addition, the adhesive layer and the structural reinforcement layer on the outside of the film layer containing the ultraviolet light absorber are also not protected. Summary of the invention
[0008] The technical problem to be solved by the present application is to provide a radiation-proof solar cell front plate and a preparation method thereof, so as to reduce or avoid the above-mentioned problems.
[0009] In order to solve the above technical problems, the present application proposes a radiation-proof solar cell front plate, which at least includes a PET film, and the PET film is bonded to a fluorocarbon resin protective film through an adhesive layer; wherein a layer of radiation-proof coating is arranged on the outer side of the fluorocarbon resin protective film, and the radiation-proof coating is formed by curing a radiation-proof coating liquid composed of the following components in parts by weight: 20-40 parts by weight of ethylene-vinyl acetate copolymer resin, 20-40 parts by weight of polybutadiene polyurethane, and 100-180 parts by weight of polyacrylate resin, 10-30 parts by weight of dimethyl sulfoxide, 4-8 parts by weight of a composite ultraviolet light absorber, 25-45 parts by weight of dipentaerythritol pentahexaacrylate active monomer, and 0.4-0.8 parts by weight of an initiator which is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide; the composite ultraviolet light absorber is composed of 50 wt% of modified 2-hydroxy-4-methoxybenzophenone and 50 wt% of 2-(2'-hydroxy-5'-tert-octylphenyl)-benzotriazole.
[0010] The present application also proposes a method for preparing the above-mentioned radiation-proof solar cell backplane, comprising the following steps: applying a radiation-proof coating liquid on the outermost side of the fluorocarbon resin protective film of a film layer formed by bonding a PET film and a fluorocarbon resin protective film together through an adhesive layer, irradiating the bonded PET film and the fluorocarbon resin protective film with ultraviolet light for 30-120 seconds; then heating to 75-85°C for further curing for 180-300 seconds; then cooling to 55-60°C for 300 seconds, and naturally cooling to room temperature to prepare a radiation-proof solar cell front panel.
[0011] Preferably, the preparation method further comprises the steps of preparing the radiation protection coating liquid: mixing 20-40 parts by weight of ethylene-vinyl acetate copolymer resin and 20-40 parts by weight of polybutadiene polyurethane, adding 10-30 parts by weight of dimethyl sulfoxide, stirring at a speed of 200-300 rpm for 30-60 minutes to obtain a first mixed liquid; mixing 100-180 parts by weight of polyacrylate resin and 25-45 parts by weight of dipentaerythritol pentahexaacrylate active monomer, stirring at a speed of 200-300 rpm for 30-60 minutes to obtain a second mixed liquid; adding the first mixed liquid and the second mixed liquid to a reactor, then adding 4-8 parts by weight of a composite ultraviolet light absorber and 0.4-0.8 parts by weight of an initiator, and mixing at a speed of 1500-2000 rpm for 30-60 minutes to prepare the radiation protection coating liquid.
[0012] Preferably, the preparation method further comprises the step of uniformly mixing the modified 2-hydroxy-4-methoxybenzophenone and 2-(2′-hydroxy-5′-tert-octylphenyl)-benzotriazole at a weight ratio of 1:1 to prepare a composite ultraviolet light absorber.
[0013] Preferably, the preparation method further comprises the step of surface-modifying 2-hydroxy-4-methoxybenzophenone, comprising: fully dissolving 2-hydroxy-4-methoxybenzophenone in ethanol to form a dissolved mixture, then adding the dissolved mixture to a polyvinyl alcohol aqueous solution, stirring continuously for 60-120 minutes to fully disperse; then adding sodium tripolyphosphate and continuing stirring for 60-120 minutes to fully mix to obtain a dispersed mixture; subjecting the dispersed mixture to freeze-drying and spraying to obtain a surface-modified solid particle mixture; adding the obtained solid particle mixture to clean water, washing and filtering for multiple times to obtain a dispersion liquid having a solid content of 20-40wt% and containing no soluble matter, and freeze-drying and spraying the dispersion liquid again to obtain modified 2-hydroxy-4-methoxybenzophenone.
[0014] Furthermore, the step of surface-modifying 2-hydroxy-4-methoxybenzophenone comprises: fully dissolving 450-500 parts by weight of 2-hydroxy-4-methoxybenzophenone in ethanol to form a dissolved mixture, then adding the dissolved mixture to a polyvinyl alcohol aqueous solution having a polyvinyl alcohol content of 10wt%-15wt%, and continuously stirring for 60-120 minutes to fully disperse; then adding 100-250 parts by weight of sodium tripolyphosphate and continuing to stir for 60-120 minutes to fully mix to obtain a dispersed mixture; subjecting the dispersed mixture to freeze-drying and spraying to obtain a surface-modified solid particle mixture; adding the obtained solid particle mixture to clean water for multiple washing and filtering to obtain a dispersion having a solid content of 20-40wt% and containing no soluble matter, and subjecting the dispersion to freeze-drying and spraying again to obtain modified 2-hydroxy-4-methoxybenzophenone.
[0015] The radiation-proof solar cell front panel of the present application can obtain excellent radiation protection performance by coating a layer of radiation-proof coating on the outermost side of the front panel, through the combination of ultraviolet light curing and thermal curing process and the combination of composite ultraviolet light absorber, while having good uniformity and visible light transmittance. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The following drawings are only intended to illustrate and explain the present application, and do not limit the scope of the present application.
[0017] Figure 1 Shown is a schematic structural diagram of a radiation-proof solar cell front panel according to a specific embodiment of the present application. DETAILED DESCRIPTION
[0018] In order to have a clearer understanding of the technical features, purposes and effects of the present application, the specific implementation of the present application is now described with reference to the accompanying drawings, wherein the same components are numbered the same.
[0019] In view of the radiation protection problem of the solar cell front plate described in the background technology, the present application proposes a radiation protection solar cell front plate, which at least includes a PET film 10, and the PET film 10 is bonded to a fluorocarbon resin protective film 30 through an adhesive layer 20. The fluorocarbon resin protective film 30 faces the sun and can provide excellent barrier properties and weather resistance. The PET film 10 provides a supporting skeleton for the entire front plate, and a weather-resistant coating or a protective layer can be further provided on the inner side of the PET film 10. The fluorocarbon resin includes but is not limited to polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polychlorotrifluoroethylene (FEVE) and / or polyvinyl fluoride (PVF).
[0020] Furthermore, a radiation protection coating 40 is further provided on the outer side of the fluorocarbon resin protective film 30, and the radiation protection coating 40 is formed by curing a radiation protection coating liquid composed of the following components in parts by weight: 20-40 parts by weight of ethylene-vinyl acetate copolymer resin, 20-40 parts by weight of polybutadiene polyurethane, 100-180 parts by weight of polyacrylate resin, 10-30 parts by weight of dimethyl sulfoxide, 4-8 parts by weight of composite ultraviolet light absorber, 25-45 parts by weight of dipentaerythritol pentahexaacrylate active monomer, and 0.4-0.8 parts by weight of initiator 2,4,6-trimethylbenzoyl-diphenylphosphine oxide. Wherein, the composite ultraviolet light absorber is composed of 50wt% of modified 2-hydroxy-4-methoxybenzophenone and 50wt% of 2-(2'-hydroxy-5'-tert-octylphenyl)-benzotriazole.
[0021] Further, the radiation protection coating liquid of the present application can be prepared by the following method, which includes the following steps: 20-40 parts by weight of ethylene-vinyl acetate copolymer resin and 20-40 parts by weight of polybutadiene polyurethane are mixed, 10-30 parts by weight of dimethyl sulfoxide are added, and the mixture is stirred at a speed of 200-300 rpm for 30-60 minutes to obtain a first mixed liquid. 100-180 parts by weight of polyacrylate resin and 25-45 parts by weight of dipentaerythritol pentahexaacrylate active monomer are mixed and stirred at a speed of 200-300 rpm for 30-60 minutes to obtain a second mixed liquid. The first mixed liquid and the second mixed liquid are added to a reactor, and then 4-8 parts by weight of a composite ultraviolet light absorber and 0.4-0.8 parts by weight of an initiator are added, and the mixture is mixed at a speed of 1500-2000 rpm for 30-60 minutes to prepare the radiation protection coating liquid of the present application.
[0022] As mentioned above, the composite ultraviolet light absorber is composed of modified 2-hydroxy-4-methoxybenzophenone and 2-(2′-hydroxy-5′-tert-octylphenyl)-benzotriazole in a weight ratio of 1:1. Wherein, the modified 2-hydroxy-4-methoxybenzophenone is a surface-modified 10-20nm particle. The composite ultraviolet light absorber of the present application has an absorption effect on the ultraviolet UVA band, can effectively quench the energy of excited state polymers, and strongly absorbs ultraviolet light with a wavelength range of 280 to 380nm.
[0023] In a specific embodiment of the present application, the present application performs surface modification treatment on 2-hydroxy-4-methoxybenzophenone as follows: fully dissolve 2-hydroxy-4-methoxybenzophenone in ethanol to form a dissolved mixture, then add the dissolved mixture to a polyvinyl alcohol aqueous solution, continue stirring for 60-120 minutes to fully disperse; then add sodium tripolyphosphate and continue stirring for 60-120 minutes to fully mix to obtain a dispersed mixture; freeze-dry and spray the dispersed mixture to obtain a surface-modified solid particle mixture; add the obtained solid particle mixture to clean water for multiple washing and filtration to obtain a dispersion having a solid content of 20-40wt% without soluble matter, and freeze-dry and spray the dispersion again to obtain modified 2-hydroxy-4-methoxybenzophenone. Wherein, the content of polyvinyl alcohol in the polyvinyl alcohol aqueous solution is 10wt%-15wt%.
[0024] Example 1
[0025] 500 parts by weight of 2-hydroxy-4-methoxybenzophenone is added to 2500 parts by weight of ethanol to fully dissolve and obtain a dissolved mixture. The dissolved mixture is added to 30,000 parts by weight of a polyvinyl alcohol aqueous solution (the content of polyvinyl alcohol in the polyvinyl alcohol aqueous solution is 10wt%) and stirred for 60 minutes. Then 250 parts by weight of sodium tripolyphosphate is added, and stirring is continued for 60 minutes to fully mix to obtain a dispersed mixture; finally, the dispersed mixture is freeze-dried and sprayed to obtain a surface-modified solid particle mixture. The obtained solid particle mixture is added to clean water and washed and filtered several times to obtain a dispersion liquid with a solid content of 20wt% without soluble matter, and the dispersion liquid is freeze-dried and sprayed again, and particles with a particle size of 10nm are screened to obtain modified 2-hydroxy-4-methoxybenzophenone. The obtained modified 2-hydroxy-4-methoxybenzophenone and 2-(2′-hydroxy-5′-tert-octylphenyl)-benzotriazole are uniformly mixed in a weight ratio of 1:1 to prepare a composite ultraviolet light absorber.
[0026] Comparative Example 1
[0027] 2-Hydroxy-4-methoxybenzophenone is used directly as an ultraviolet light absorber without modification, and 2-(2'-hydroxy-5'-tert-octylphenyl)-benzotriazole is not added.
[0028] Example 2
[0029] 450 parts by weight of 2-hydroxy-4-methoxybenzophenone is added to 2000 parts by weight of ethanol to fully dissolve and obtain a dissolved mixture. The dissolved mixture is added to 25000 parts by weight of polyvinyl alcohol aqueous solution (the content of polyvinyl alcohol in the polyvinyl alcohol aqueous solution is 15wt%) and stirred for 120 minutes. Then 100 parts by weight of sodium tripolyphosphate is added, and stirring is continued for 120 minutes to fully mix to obtain a dispersed mixture; finally, the dispersed mixture is freeze-dried and sprayed to obtain a surface-modified solid particle mixture. The obtained solid particle mixture is added to clean water and washed and filtered several times to obtain a dispersion liquid with a solid content of 40wt% without soluble matter, and the dispersion liquid is freeze-dried and sprayed again, and particles with a particle size of 20nm are screened to obtain modified 2-hydroxy-4-methoxybenzophenone. The obtained modified 2-hydroxy-4-methoxybenzophenone and 2-(2'-hydroxy-5'-tert-octylphenyl)-benzotriazole are uniformly mixed in a weight ratio of 1:1 to prepare a composite ultraviolet light absorber.
[0030] Comparative Example 2
[0031] 2-(2′-hydroxy-5′-tert-octylphenyl)-benzotriazole was used directly as the ultraviolet light absorber without adding modified 2-hydroxy-4-methoxybenzophenone.
[0032] Embodiment 3-5
[0033] According to the raw material weight parts and parameters in the table below, radiation protection coating liquids were prepared according to the above methods.
[0034] Example 3 Example 4 Example 5 Ethylene-vinyl acetate copolymer resin 20 30 40 Polybutadiene polyurethane 20 30 40 Dimethyl sulfoxide 10 20 30 Polyacrylate resin 100 140 180 Dipentaerythritol pentahexaacrylate 25 35 45 Composite UV absorber 4 6 8 Initiator 0.4 0.6 0.8
[0035] Among them, Example 3 and Example 5 use the composite ultraviolet light absorber prepared in Example 1, and Example 4 uses the composite ultraviolet light absorber prepared in Example 2.
[0036] Comparative Examples 3-5
[0037] According to the method of the above embodiment, a comparative radiation protection coating liquid was prepared according to the raw material weight parts and parameters in the following table.
[0038] Comparative Example 3 Comparative Example 4 Comparative Example 5 Ethylene-vinyl acetate copolymer resin 20 0 40 Polybutadiene polyurethane 20 30 0 Dimethyl sulfoxide 0 20 30 Polyacrylate resin 100 140 180 Dipentaerythritol pentahexaacrylate 25 35 45 UV absorber 4 6 8 Initiator 0.4 0.6 0.8
[0039] Among them, Comparative Examples 3 and 5 use the ultraviolet light absorber of Comparative Example 1, and Comparative Example 4 uses the ultraviolet light absorber of Comparative Example 2.
[0040] The radiation protection coating liquids of Examples 3-5 and Comparative Examples 3-5 are respectively coated on the outermost side of the fluorocarbon resin protective film 30 of the film layer bonded into one by the PET film 10 and the fluorocarbon resin protective film 30 through the adhesive layer 20, and the bonded PET film 10 and the fluorocarbon resin protective film 30 are irradiated with ultraviolet light for 30-120 seconds; then the temperature is raised to 75-85°C for further curing for 180-300 seconds; then the temperature is lowered to 55-60°C for 300 seconds, and naturally cooled to room temperature to prepare a radiation protection solar cell front plate. The present application first performs rapid pre-curing by ultraviolet light at room temperature, and then increases the temperature for temperature-raising curing. While temperature-raising curing, the stress in the pre-curing process is released, and after temperature-raising curing, heat preservation annealing is performed to reduce stress concentration in bonding and avoid warping and deformation of the film layer.
[0041] The PET film 10 is a biaxially stretched PET film with a thickness of 100-200 μm, the fluorocarbon resin protective film 30 is a PVDF film with a thickness of 10-20 μm, and the adhesive layer 20 is cured by a commercially available transparent EVA adhesive, and the thickness of the adhesive layer 20 is 3-5 μm.
[0042] The front plate prepared above was subjected to an accelerated aging test at 120° C. for 48 hours, with a test humidity of 100%, and a test of visible light transmittance % and transmittance % of ultraviolet light of different wavelengths. The test results are shown in the following table. 280nm 320nm 340nm 380nm Visible light transmittance Example 3 <5 <5 <5 <5 91 Example 4 <5 <5 <5 <5 92 Example 5 <5 <5 <5 <5 93 Comparative Example 3 >10 >10 >10 >10 82 Comparative Example 4 >10 >10 >10 >10 92 Comparative Example 5 >10 >10 >10 >10 83
[0043] The results show that the radiation-proof solar cell front panel of the present application has both excellent visible light transmittance and good radiation protection performance.
[0044] In addition, the prepared radiation-proof solar cell front plate is divided into regions, and the film pieces of different divided regions are cut to test the consistency of the film. The test shows that the performance difference rate of each film piece of the film of Examples 3-5 is less than 3%, while the performance difference rate of each film piece of the film of Comparative Examples 3-5 is relatively large, which is 15%, 3%, and 12% respectively. The results show that the ultraviolet light absorption performance of the radiation-proof solar cell front plate of the present application is excellent, and has good uniformity, indicating that the ultraviolet light absorption component of the present invention has good dispersibility.
[0045] Those skilled in the art should understand that although the present application is described in the form of multiple embodiments, not every embodiment contains only one independent technical solution. Such description in the specification is only for the sake of clarity, and those skilled in the art should understand the specification as a whole and regard the technical solutions involved in each embodiment as being able to be combined into different embodiments to understand the scope of protection of the present application.
[0046] The above description is only an illustrative embodiment of the present application and is not intended to limit the scope of the present application. Any equivalent changes, modifications and combinations made by any technician in the field without departing from the concept and principle of the present application shall fall within the scope of protection of the present application.
Claims
1. A radiation-proof solar cell front plate, comprising at least a PET film (10), wherein the PET film (10) is bonded to a fluorocarbon resin protective film (30) via an adhesive layer (20); characterized in that: A layer of radiation protection coating (40) is arranged on the outer side of the fluorocarbon resin protective film (30), and the radiation protection coating (40) is formed by curing a radiation protection coating liquid composed of the following components in parts by weight: 20-40 parts by weight of ethylene-vinyl acetate copolymer resin, 20-40 parts by weight of polybutadiene polyurethane, 100-180 parts by weight of polyacrylate resin, 10-30 parts by weight of dimethyl sulfoxide, 4-8 parts by weight of composite ultraviolet light absorber, 25-45 parts by weight of dipentaerythritol pentahexaacrylate active monomer, and 0.4-0.8 parts by weight of initiator which is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide; the composite ultraviolet light absorber is composed of 50 wt% of modified 2-hydroxy-4-methoxybenzophenone and 50 wt% of 2-(2'-hydroxy-5'-tert-octylphenyl)-benzotriazole.
2. A method for preparing a radiation-proof solar cell front plate as claimed in claim 1, comprising the following steps: applying a radiation-proof coating liquid on the outermost side of the fluorocarbon resin protective film (30) of a film layer in which a PET film (10) and a fluorocarbon resin protective film (30) are bonded into one by an adhesive layer (20), irradiating the bonded PET film (10) and the fluorocarbon resin protective film (30) with ultraviolet light for 30-120 seconds; then heating to 75-85°C for further curing for 180-300 seconds; then cooling to 55-60°C for 300 seconds, and naturally cooling to room temperature to prepare a radiation-proof solar cell front plate.
3. The preparation method according to claim 2, characterized in that: The method further comprises the steps of preparing the radiation-proof coating liquid: mixing 20-40 parts by weight of ethylene-vinyl acetate copolymer resin and 20-40 parts by weight of polybutadiene polyurethane, adding 10-30 parts by weight of dimethyl sulfoxide, stirring at a rotation speed of 200-300 rpm for 30-60 minutes to obtain a first mixed liquid; mixing 100-180 parts by weight of polyacrylate resin and 25-45 parts by weight of dipentaerythritol pentahexaacrylate active monomer, stirring at a rotation speed of 200-300 rpm for 30-60 minutes to obtain a second mixed liquid; adding the first mixed liquid and the second mixed liquid into a reaction kettle, then adding 4-8 parts by weight of a composite ultraviolet light absorber and 0.4-0.8 parts by weight of an initiator, and mixing at a rotation speed of 1500-2000 rpm for 30-60 minutes to prepare the radiation-proof coating liquid.
4. The preparation method according to claim 3, characterized in that: The method further comprises the step of uniformly mixing the modified 2-hydroxy-4-methoxybenzophenone and 2-(2'-hydroxy-5'-tert-octylphenyl)-benzotriazole at a weight ratio of 1:1 to prepare a composite ultraviolet light absorber.
5. The preparation method according to claim 4, characterized in that: The method further comprises the step of performing surface modification treatment on 2-hydroxy-4-methoxybenzophenone, comprising: fully dissolving 2-hydroxy-4-methoxybenzophenone in ethanol to form a dissolved mixture, then adding the dissolved mixture to a polyvinyl alcohol aqueous solution, stirring continuously for 60-120 minutes to fully disperse the mixture; then adding sodium tripolyphosphate and stirring continuously for 60-120 minutes to fully mix the mixture to obtain a dispersed mixture; subjecting the dispersed mixture to freeze-drying and spraying to obtain a surface-modified solid particle mixture; adding the obtained solid particle mixture to clean water, washing and filtering the mixture for multiple times to obtain a dispersed liquid having a solid content of 20-40 wt% and containing no soluble matter, and subjecting the dispersed liquid to freeze-drying and spraying again to obtain modified 2-hydroxy-4-methoxybenzophenone.
Citation Information
Patent Citations
A POE-containing solar cell backsheet and its preparation method
CN102867872B
Photovoltaic assembly
CN106952978A
An encapsulating film, its preparation method and application
CN112812695B
Radiation proof double glass surface solar cell module
CN203134840U
Water-based high ultraviolet blocking paint
CN103740244A